2019
DOI: 10.1002/jor.24410
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Acute Anterior Cruciate Ligament Tears on Peri‐Articular Bone in Human Knees Within the First Year of Injury

Abstract: Anterior cruciate ligament (ACL) tears are common sports‐related knee injuries that increase the risk of developing post‐traumatic osteoarthritis. ACL tears are rarely an isolated injury but are often associated with traumatic bone marrow lesions (BMLs). While early loss of bone mass following the ACL injury has been previously described, to date, microarchitectural information has not been reported due to the limited resolution of clinical imaging systems. In this study, we provide the first evidence of detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…It can also be expected here that advances in technology and image processing may enable similar evaluation protocols in human diagnostic imaging. To further add value to the approach, the method could be tested with high-resolution peripheral quantitative CT (HRpQCT) scans for peripheral infections, since the resolution of HRpQCT (60 µm) is sufficient to monitor bone changes in fracture repair or in joint degeneration 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…It can also be expected here that advances in technology and image processing may enable similar evaluation protocols in human diagnostic imaging. To further add value to the approach, the method could be tested with high-resolution peripheral quantitative CT (HRpQCT) scans for peripheral infections, since the resolution of HRpQCT (60 µm) is sufficient to monitor bone changes in fracture repair or in joint degeneration 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior clinical studies have demonstrated a compartment/region-dependent loss of periarticular bone mass and/or bone mineral density following traumatic joint injury 37-42 . Several of these studies indicate incomplete recovery of bony deficits in the long-term, with some evidence even indicating lower BMD in the injured limb 10+ years after knee injury.…”
Section: Discussionmentioning
confidence: 99%
“…performed and analyzed all scans using the standard manufacturer’s method 7 for the primary morphological parameters described here. 33…”
Section: Methodsmentioning
confidence: 99%
“…8,22,25,26 In addition, BMD changes and subchondral bone changes have been observed after full ACL rupture in human studies. 33,55,57…”
mentioning
confidence: 99%